A Novel Animal Model for Regional Microbial Dysbiosis of the Pioneer Microbial Community - Malmuthuge, Nilusha; Griebel, Philip J. (Frontiers in Microbiology, 2019)
Pioneer microbiota colonizing the newborn gastrointestinal tract has long-lasting effects on host health. Restoration of the gut microbial community, following dysbiosis during the neonatal period, may be one strategy to prevent undesirable health outcomes linked to an altered neonatal gut microbiome. Without appropriate animal models that recreate the prolonged human neonatal developmental period it is not possible to effectively analyze interventions designed to restore regional microbial populations. Our study used a lamb model in which intestinal segments were surgically isolated (blind-ended) in fetal lambs to create early microbial dysbiosis by delaying post-natal exposure to intestinal ingesta. Intestinal segments isolated in utero retained blood flow, innervation, and lymphatic drainage through the mesenteric attachment. Continuity of the fetal gastro-intestinal tract was re-established by side-to-side anastomosis of intestine proximal and distal to each isolated intestinal segment. Microbial restoration was then implemented in neonatal lambs by reconnecting a portion of the in utero isolated intestinal segments to adjacent intestinal tract one and seven days after birth. Bacterial communities colonizing the adjacent intestine, in utero isolated intestinal segments, and reconnected intestinal segments were profiled using 16S amplicon sequencing on days 1, 7, and 56 of age. The in utero isolated intestinal segments were colonized one day after birth but the density of active bacteria was reduced and community composition altered when compared to adjacent intestine. Proteobacteria dominated the adjacent small intestine at early time points (day 1 and day 7) with a shift to primarily Firmicutes on day 56, consistent with establishment of an anaerobic bacterial community. In contrast, Proteobacteria persisted as the predominant community for 56 days in the in utero isolated intestinal segments. There was, however, almost full restoration of the microbial community composition in the in utero isolated intestinal segments following reconnection to the adjacent intestine. The density of beneficial bacteria, especially Bifidobacterium, remained significantly lower in the reconnected intestinal segments at 56 days when compared to adjacent intestine. Post-natal persistence of a stable pioneer community (Proteobacteria) in the in utero isolated intestinal segments provides a model system to study the temporal effects of regional microbial dysbiosis throughout a prolonged neonatal period.